Determinants of Tax Revenue in Ethiopia (Johansen Co-Integration Approach) - Ayenew, Workineh (International Journal of Business, Economics and Management, 2016)
Tax revenue in Ethiopia has been low throughout the study period (1974 to 2013). Tax revenue in Ethiopia was below the average of sub Saharan African countries. The main objective of this study is to empirically examine the major determinants of tax revenue in Ethiopia for the period ranging from 1975-2013, using Johansen maximum likelihood co-integration approach. The result revealed that in the long run real GDP per capita income, foreign aid and industrial value added share of GDP positively and significantly affect tax revenue. However, inflation exerted a negative and significant influence. Whereas, in the short run Real GDP per capita income and inflation have negative effect, whereas industrial Value added share of GDP has positive effect on tax revenue in Ethiopia. The sign of real gross domestic product per capita income is contrary to the priori expectation. Moreover, the coefficients of the lagged error correction term (ECM (-1)) is significant and negative as expected, which imply the existence of economic or government forces that restore the long run equilibrium from short run shocks. Finally, the study recommends measures such as a boost in per capita income growth, structural transformations, introduction of new tax bases and efficient utilization of foreign aid inflow have to be considered by the concerned bodies so as to bring efficient tax administration and enhance revenue growth. Moreover, the government shall give a due recognition to the development of the industrial sector.